Ag27 nano-cluster photosensitizer as well as preparation method and application thereof

By preparing and loading the Ag27 nanocluster photosensitizer on TiO2, Ag27@TiO2 composite photocatalytic material is formed, which solves the problem of low photocatalytic activity of metal nanocluster photosensitizer and TiO2 composite materials in the prior art, and achieves high-efficiency photocatalytic hydrogen production and formaldehyde generation.

CN119775291AActive Publication Date: 2025-04-08ANHUI UNIVERSITY OF TRADITIONAL CHINESE MEDICINE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510203912.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-08
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The existing metal nanocluster photosensitizers with accurate structures are difficult to form high-performance composite photocatalytic materials with TiO2, resulting in low photocatalytic hydrogen production activity.

Method used

A Ag27 nanocluster photosensitizer was prepared with the chemical formula C170H167Ag27Cl2N18O6P7. Through specific organic ligand composition and preparation methods, Ag27 nanoclusters of monoclinic crystal were formed, and supported on TiO2 to form Ag27@TiO2 composite photocatalytic material.

Benefits of technology

Under LED lighting conditions at 365nm wavelength, the Ag27@TiO2 composite material significantly improves the photogenerated electron-hole separation efficiency, achieves high-efficiency photocatalytic hydrogen production, with a hydrogen production rate of 15.77mmol·g-1·h-1, and a significant increase in formaldehyde content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775291A_ABST
    Figure CN119775291A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of crossing of nano materials and coordination chemistry, and particularly relates to an Ag27 nano-cluster photosensitizer as well as a preparation method and application thereof. The chemical formula of the Ag27 nano-cluster photosensitizer is C170H167Ag27Cl2N18O6P7, the chemical formula is abbreviated as Ag27 (DPCA) 6 (DPP) 3 (DPPB) 2 (Ac) 3Cl2, and the Ag27 nano-cluster photosensitizer belongs to a monoclinic system; according to the present invention, the space group is C2, the # imgabs0 # alpha is 90 DEG, the beta is 112.278 (7) DEG, and the gamma is 90 DEG, and the composite photocatalytic material Ag27-coated TiO2 formed by the # imgabs1 # Ag27 nano-cluster photosensitizer and the TiO2 has excellent hydrogen production activity, and can oxidize the methanol sacrificial agent into the high value-added product formaldehyde. Under the condition of LED illumination with the wavelength of 365 nm, the photocatalytic hydrogen production rate of 1% Ag27-coated TiO2 and the content of formaldehyde in a solution are respectively 12.13 times and 10.70 times that of TiO2, and the 1% Ag27-coated TiO2 has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the cross-field of nanomaterials and coordination chemistry, and in particular relates to an Ag 27 Nanocluster photosensitizer and its preparation method and application. Background Art

[0002] With the increasing depletion of fossil fuel resources and the intensification of global warming, human energy supply is gradually transforming from dependence on fossil fuels to clean and renewable energy. Hydrogen, as an ideal clean energy carrier, only produces water during combustion without any pollutant emissions, and is regarded as a highly promising alternative energy source in the future. As one of the largest renewable energy sources on earth, photocatalytic hydrogen production from sunlight is also considered to be a cleaner, more efficient and sustainable method of hydrogen production. Among many photocatalytic materials, TiO2 is regarded as an ideal environmentally friendly photocatalytic material due to its stable chemical properties, high melting point, easy doping and modification, non-toxicity, and low price. Although TiO2 has excellent physical and chemical properties, its photogenerated electrons and holes are easy to recombine, resulting in a shortened lifetime of photogenerated carriers, which limits its photocatalytic performance.

[0003] In recent years, atomically precise metal nanoclusters, as a new type of photosensitizer, not only have strong absorption capacity for visible light, but also have high specific surface area and abundant surface active sites. The composite photocatalytic materials formed by loading them on TiO2 show significantly enhanced photogenerated electron-hole separation ability and photocatalytic performance. In particular, their determined atomic structure composition provides an ideal model for in-depth study of the complex relationship between catalyst structure and performance. For example, Tian et al. 12 The nanoclusters are uniformly loaded on TiO2 nanoparticles, and the photocatalytic hydrogen evolution rate reaches 5.6 mmol·h -1 ·g -1 Bootharaju et al. 12 Ag 32 (SePh) 30 ] 4- Nanoclusters are loaded on the TiO2 surface, and the photocatalytic hydrogen production activity reaches 6.810 mmol·h -1 ·g -1 Wang et al. 44 (SR) 30 The photocatalytic rate of H2 generation by nanoclusters loaded on TiO2 is 7.4 mmol·h -1 ·g -1However, the composite photocatalytic materials formed by metal nanoclusters with precise structures and TiO2 reported in existing literature have low photocatalytic activity and generally low hydrogen production rates. Therefore, it is a key issue to be solved urgently to prepare metal nanocluster photosensitizers with precise structures that can form high-performance composite photocatalytic materials with TiO2, improve photocatalytic activity, and achieve efficient photocatalytic hydrogen production. Summary of the invention

[0004] One of the purposes of the present invention is to provide a Ag 27 Nanocluster photosensitizers effectively solve the technical problem that existing metal nanocluster photosensitizers are difficult to form high-performance composite photocatalytic materials with TiO2 for efficient photocatalytic hydrogen production. This is because Ag 27 The nanocluster photosensitizer exhibits strong absorption near 365nm, and can effectively excite Ag under 365nm LED illumination. 27 The electrons in the nanocluster photosensitizer transition from the ground state to the excited state, which is beneficial for the TiO2 carrier to improve the efficiency of photogenerated electron-hole separation, thereby achieving efficient photocatalytic hydrogen production.

[0005] To achieve the above object, the present invention adopts the following technical solution: an Ag 27 Nanocluster photosensitizer, the Ag 27 The chemical formula of the nanocluster photosensitizer is C 170 H 167 Ag 27 Cl2N 18 O6P7, composed of 27 Ag atoms, 3 DPP organic ligands, 6 DPCA organic ligands, 2 DPPB organic ligands, 3 Ac ligands and 2 Cl halogen ligands, is abbreviated as Ag 27 (DPCA)6(DPP)3(DPPB)2(Ac)3Cl2, belongs to the monoclinic system; the space group is C2, α=90°, β=112.278(7)°, γ=90°, The molecular weight is 5758.39Da;

[0006] The organic ligand DPCA is deprotonated bis(2-pyridylmethyl)amine, the organic ligand DPP is deprotonated diphenylphosphine, the organic ligand DPPB is 1,4-bis(diphenylphosphino)butane, and the ligand Ac is CH3COO - , the structural formulas of the organic ligands DPP, DPCA and DPPB are shown in the following figures:

[0007]

[0008] As Ag 27 Further improvements of nanocluster photosensitizers:

[0009] Preferably, the Ag 27 Two twisted Ag in nanocluster photosensitizer 13 Icosahedrons are fused together to form Ag by sharing triangular faces 23 , the remaining 4 Ag atoms are respectively 23 The two Ag atoms in the core, the P atom in the diphenylphosphine ligand, and the two N atoms in the bis(2-pyridylmethyl)amine ligand form four μ5-Ag sites. 23 Together with 4 μ5-Ag, it forms the core Ag of the cluster 27 .

[0010] The second object of the present invention is to provide an Ag as described in any one of the above 27 The preparation method of the nanocluster photosensitizer comprises the following steps:

[0011] S1. Dissolve the silver salt in a mixed solvent of dichloromethane and methanol, add the monophosphine ligand and the diphosphine ligand, stir, then add the nitrogen ligand and acetic acid, continue to stir well, add the sodium borohydride aqueous solution, stir well at room temperature in the dark, and obtain a green clear solution;

[0012] S2, using ether as a diffusion agent, gas phase diffusion is carried out into the green clear solution to obtain crystals, collecting the crystal products, washing with ether and vacuum drying to obtain Ag. 27 Nanocluster photosensitizers.

[0013] As Ag 27 The preparation method of nanocluster photosensitizer is further improved:

[0014] Preferably, the molar mass ratio of the silver salt, the monophosphine ligand, the diphosphine ligand, the nitrogen ligand, the acetic acid and the sodium borohydride contained in the sodium borohydride aqueous solution is 1:(0.6-1.3):(1.2-1.7):(0.4-1):(2-4):(12-20).

[0015] Preferably, in step S1, the mixed solvent of dichloromethane and methanol is prepared by mixing dichloromethane and methanol in a volume ratio of (4-5):1.

[0016] Preferably, in step S1, the silver salt is dissolved in a mixed solvent of dichloromethane and methanol at a concentration of 0.009-0.012 mmol / ml.

[0017] Preferably, the silver salt is silver trifluoromethanesulfonate; or, the monophosphine ligand is diphenylphosphine hydrogen; or, the diphosphine ligand is 1,4-bis(diphenylphosphino)butane; or, the nitrogen ligand is bis(2-pyridylmethyl)amine.

[0018] The second object of the present invention is to provide an Ag as described in any one of the above 27 Application of nanocluster photosensitizers in photocatalytic hydrogen production.

[0019] As Ag 27 Further improvements in the application of nanocluster photosensitizers in photocatalytic hydrogen production:

[0020] Preferably, Ag 27 Nanocluster photosensitizers loaded on TiO2 were applied in photocatalytic hydrogen production.

[0021] Preferably, Ag 27 The loading rate of nanocluster photosensitizer on TiO2 was 1%.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1) The present invention provides a structured Ag 27 Nanocluster photosensitizer, chemical formula C 170 H 167 Ag 27 Cl2N 18 O6P7, Ag 27 The nanocluster photosensitizer exhibits strong absorption near 365nm, and can effectively excite Ag under 365nm LED illumination. 27 The electrons in the nanocluster photosensitizer transition from the ground state to the excited state, which is beneficial for the TiO2 carrier to improve the efficiency of photogenerated electron-hole separation, thereby achieving efficient photocatalytic hydrogen production.

[0024] 2) The present invention provides an Ag 27 The preparation method of the nanocluster photosensitizer, the nitrogen ligand (bis(2-pyridylmethyl)amine) and the bisphosphine ligand (1,4-bis(diphenylphosphino)butane) are both flexible ligands, wherein the nitrogen ligand (bis(2-pyridylmethyl)amine) contains three nitrogen atoms in its molecular structure, and the bisphosphine ligand (1,4-bis(diphenylphosphino)butane) contains two phosphine atoms in its molecular structure, and these nitrogen atoms and phosphine atoms can form stable coordination bonds with metals, thereby stabilizing metal clusters during the catalytic process. The flexible chains in the nitrogen ligand (bis(2-pyridylmethyl)amine) and the bisphosphine ligand (1,4-bis(diphenylphosphino)butane) enable them to rotate and bend freely during the catalytic process, thereby better adapting to different reaction environments and substrates, enhancing the binding energy with the substrate, and improving the photocatalytic efficiency.

[0025] 3) Ag of the present invention 27 Nanocluster photosensitizers can form high-performance composite photocatalytic materials Ag with TiO2 27@TiO2. Not only does it have excellent hydrogen production activity, but it can also oxidize methanol sacrificial agent into high value-added product formaldehyde. Under the condition of LED light with a wavelength of 365nm, the loading rate is 1% Ag 27 The photocatalytic hydrogen production rate of @TiO2 is as high as 15.77mmol·g -1 ·h -1 , the formaldehyde content of the solution is as high as 37.68mmol / L, which is 12.13 times and 10.70 times that of the pure TiO2 carrier without photosensitizer loading, respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Ag prepared in Example 1-5 27 Precise structure and size map of nanoclusters, including Ag 27 Overall structure of nanoclusters, removal of Ag 27 Peripheral ligand diagram, Ag excluding C and H atoms 27 Schematic diagram of coordinated atoms and Ag 27 Kernel schematic diagram;

[0027] Figure 2 Ag prepared in Example 1-5 27 UV–visible absorption spectra of nanocluster solutions;

[0028] Figure 3 Ag with different loading rates prepared in Example 6 27 @Linear relationship between TiO2 hydrogen production and illumination time;

[0029] Figure 4 Ag with different loading rates prepared in Example 6 27 @Hydrogen production performance diagram of TiO2 under 365nm light;

[0030] Figure 5 Ag with different loading rates prepared in Example 6 27 @Schematic diagram of the determination of formaldehyde content in the solution after photocatalytic hydrogen production by TiO2. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] This embodiment provides an Ag 27 The preparation method of the nanocluster photosensitizer specifically comprises the following steps:

[0034] S1. Dissolve 15 mg of silver trifluoromethanesulfonate (0.058 mmol) in 5 mL of dichloromethane and 1 mL of methanol, add 12 μL of diphenylphosphine (0.069 mmol) and 40 mg of 1,4-bis(diphenylphosphino)butane (0.094 mmol), stir for 30 min, add 6 μL of bis(2-pyridylmethyl)amine (0.033 mmol) and 10 μL of acetic acid (0.17 mmol) to the solution, stir well for 120 min, add 1 mL of sodium borohydride aqueous solution (concentration 30 mg / ml, containing 0.79 mmol of sodium borohydride), the solution changes from colorless to brown-black, and after stirring at room temperature for 36 h under light-proof conditions, the brown-black solution changes to a green clear solution;

[0035] The molar mass ratio of the silver salt, the monophosphine ligand, the diphosphine ligand, the nitrogen ligand, the acetic acid and the sodium borohydride contained in the sodium borohydride aqueous solution is 1:1.19:1.62:0.57:2.93:13.6.

[0036] S2, by using ether as a diffusion agent, gas phase diffusion is carried out into the green clear solution to obtain crystals, which are washed with ether, collected and dried at room temperature to obtain Ag. 27 Nanocluster photosensitizers.

[0037] Example 2

[0038] This embodiment provides an Ag 27 The preparation method of the nanocluster photosensitizer specifically comprises the following steps:

[0039] S1. Dissolve 15 mg of silver trifluoromethanesulfonate (0.058 mmol) in 5 mL of dichloromethane and 1 mL of methanol, add 10 μL of diphenylphosphine (0.057 mmol) and 30 mg of 1,4-bis(diphenylphosphino)butane (0.070 mmol), stir for 30 min, add 10 μL of bis(2-pyridylmethyl)amine (0.056 mmol) and 12 μL of acetic acid (0.21 mmol) to the solution, stir well for 120 min, add 1 mL of sodium borohydride aqueous solution (concentration 40 mg / ml, containing 1.06 mmol of sodium borohydride), the solution changes from colorless to brown-black, and after stirring at room temperature for 40 h under light-proof conditions, the brown-black solution changes to a green clear solution;

[0040] The molar mass ratio of the silver salt, the monophosphine ligand, the diphosphine ligand, the nitrogen ligand, the acetic acid and the sodium borohydride contained in the sodium borohydride aqueous solution is 1:0.98:1.21:0.97:3.62:18.3.

[0041] S2, by using ether as a diffusion agent, gas phase diffusion is carried out into the green clear solution to obtain crystals, which are washed with ether, collected and dried at room temperature to obtain Ag. 27 Nanocluster photosensitizers.

[0042] Example 3

[0043] This embodiment provides an Ag 27 The method for preparing nanoclusters specifically comprises the following steps:

[0044] S1. Dissolve 15 mg of silver trifluoromethanesulfonate (0.058 mmol) in 4 mL of dichloromethane and 1 mL of methanol, add 11 μL of diphenylphosphine (0.063 mmol) and 28 mg of 1,4-bis(diphenylphosphino)butane (0.066 mmol), stir for 30 min, add 8 μL of bis(2-pyridylmethyl)amine (0.044 mmol) and 9 μL of acetic acid (0.16 mmol) to the solution, stir well for 120 min, add 1 mL of sodium borohydride aqueous solution (concentration 35 mg / ml, containing 0.926 mmol of sodium borohydride), the solution changes from colorless to brown-black, and after stirring at room temperature for 42 h under light-proof conditions, the brown-black solution changes to a green clear solution;

[0045] The molar mass ratio of the silver salt, the monophosphine ligand, the diphosphine ligand, the nitrogen ligand, the acetic acid and the sodium borohydride contained in the sodium borohydride aqueous solution is 1:1.09:1.14:0.76:2.76:16.

[0046] S2, by using ether as a diffusion agent, gas phase diffusion is carried out into the green clear solution to obtain crystals, which are washed with ether, collected and dried at room temperature to obtain Ag. 27 Nanocluster photosensitizers.

[0047] Example 4

[0048] This embodiment provides an Ag 27 The method for preparing nanoclusters specifically comprises the following steps:

[0049] S1. Dissolve 15 mg of silver trifluoromethanesulfonate (0.058 mmol) in 4 mL of dichloromethane and 1 mL of methanol, add 7 μL of diphenylphosphine (0.040 mmol) and 35 mg of 1,4-bis(diphenylphosphino)butane (0.082 mmol), stir for 30 min, add 4.2 μL of bis(2-pyridylmethyl)amine (0.023 mmol) and 7 μL of acetic acid (0.12 mmol) to the solution, stir well for 120 min, add 1 mL of sodium borohydride aqueous solution (concentration 27 mg / ml, containing 0.714 mmol of sodium borohydride), the solution changes from colorless to brown-black, and after stirring at room temperature for 42 h under light-proof conditions, the brown-black solution changes to a green clear solution;

[0050] The molar mass ratio of the silver salt, the monophosphine ligand, the diphosphine ligand, the nitrogen ligand, the acetic acid and the sodium borohydride contained in the sodium borohydride aqueous solution is 1:0.69:1.41:0.4:2.07:12.3.

[0051] S2, by using ether as a diffusion agent, gas phase diffusion is carried out into the green clear solution to obtain crystals, which are washed with ether, collected and dried at room temperature to obtain Ag. 27 Nanocluster photosensitizers.

[0052] Example 5

[0053] This embodiment provides an Ag 27 The method for preparing nanoclusters specifically comprises the following steps:

[0054] S1. Dissolve 15 mg of silver trifluoromethanesulfonate (0.058 mmol) in 5 mL of dichloromethane and 1 mL of methanol, add 13 μL of diphenylphosphine (0.075 mmol) and 42 mg of 1,4-bis(diphenylphosphino)butane (0.098 mmol), stir for 30 min, add 10.5 μL of bis(2-pyridylmethyl)amine (0.058 mmol) and 13 μL of acetic acid (0.23 mmol) to the solution, stir well for 120 min, add 1 mL of sodium borohydride aqueous solution (concentration 44 mg / ml, containing 1.16 mmol of sodium borohydride), the solution changes from colorless to brown-black, and after stirring at room temperature for 42 h under light-proof conditions, the brown-black solution changes to a green clear solution;

[0055] The molar mass ratio of the silver salt, the monophosphine ligand, the diphosphine ligand, the nitrogen ligand, the acetic acid and the sodium borohydride contained in the sodium borohydride aqueous solution is 1:1.29:1.69:1:3.96:20.

[0056] S2, by using ether as a diffusion agent, gas phase diffusion is carried out into the green clear solution to obtain crystals, which are washed with ether, collected and dried at room temperature to obtain Ag.27 Nanocluster photosensitizers.

[0057] Take the Ag prepared in Example 1-3 27 The nanocluster photosensitizer was further characterized as follows:

[0058] The crystals prepared in Examples 1-3 were tested using a Bruker SmartApexⅡCCD single crystal X-ray diffractometer. During the test, graphite-monochromatized Ga-Kα rays (wavelength λ = ) was used as the diffraction source, and data were collected by ω scanning under nitrogen protection and low temperature conditions of 193K. Subsequently, the structure of the single crystal was solved using the ShelXT and ShelXL programs in the Olex2 software package. The refinement process was optimized using the least squares F2 method. In addition, the SADABS program was used to perform empirical absorption correction on the positions of all non-hydrogen atoms, and the positions of these non-hydrogen atoms, including silver, nitrogen, phosphorus, chlorine, oxygen and carbon, were directly determined. The positions of hydrogen atoms in the molecule were obtained through isotropic calculation processing. The solved Ag 27 The precise structure of the nanoclusters is Figure 1 As shown, it can be seen that Ag 27 The nanocluster is composed of 27 Ag atoms, 6 DPCA organic ligands, 3 DPP organic ligands, 2 DPPB organic ligands, 3 Ac ligands and 2 Cl halogen ligands; 2 of them are twisted Ag atoms. 13 Icosahedrons are fused together to form Ag by sharing triangular faces 23 , the remaining 4 Ag atoms are respectively 23 The two Ag atoms in the core, the P atom in the diphenylphosphine ligand, and the two N atoms in the bis(2-pyridylmethyl)amine ligand form four μ5-Ag sites. 23 Together with 4 μ5-Ag, it forms the core Ag of the cluster 27 The cluster size is about 2.2 nm. The detailed crystal measurement data are shown in Table 1.

[0059] Table 1 Main crystallographic data

[0060]

[0061]

[0062] R1=∑||Fo|-|Fc|| / ∑|Fo|.wR2=[∑w(F o 2 -F c 2 ) 2 / ∑w(F o 2 )2 ] 1 / 2

[0063] Example 6

[0064] In this embodiment, Ag 27 Nanoclusters were loaded on TiO2 to prepare composite photocatalytic materials, and the photocatalytic hydrogen production performance was tested:

[0065] The Ag prepared in Example 1 27 The nanoclusters were dissolved in dichloromethane to prepare a 2 mg / mL green solution. 100 mg of commercial TiO2 (commercially available P25) white powder was ultrasonically dispersed in 10 mL of dichloromethane to form a suspension. After stirring the suspension continuously, 250 uL, 500 uL, 1 mL and 2 mL of Ag were added respectively. 27 Nanocluster solution, Ag 27 The nanocluster solution quickly changed from green to colorless, and the TiO2 powder changed from white to gray. After stirring at room temperature overnight, the suspension was centrifuged at 10,000 rpm for 3 minutes to remove the colorless and transparent upper clear solution; the gray precipitate at the bottom was dried in a vacuum oven to collect Ag 27 Ag nanocluster loadings of 0.5%, 1%, 2%, and 4% 27 @TiO2 composite photocatalytic material.

[0066] A 100W LED lamp with a wavelength of 365nm was selected as the light source for the photocatalytic reaction. 27 The TiO2 composite photocatalytic material was ultrasonically dispersed in 14 ml methanol (used as a sacrificial agent) and 6 mL water, and then loaded into a 250 mL sealed quartz reactor. Before turning on the LED light, a nitrogen-argon mixed gas was passed for 30 minutes to exhaust the air. In order to monitor and analyze the amount of hydrogen produced during the reaction, an online gas chromatograph model GC9720 (manufactured by Furley Instruments) was used for real-time sampling and detection, with high-purity argon as the carrier gas. In addition, the temperature of the entire experimental system was controlled to be constant at 50 °C by using a constant temperature circulation device. After 4 h of illumination, the liquid was recovered to determine the formaldehyde content after methanol oxidation, as follows: 1 mL of the solution after the photocatalytic hydrogen production reaction was centrifuged, and the upper clear solution was diluted 10 times; then 0.5 mL of the liquid product was mixed with 2.0 mL of water and 0.5 mL of the reagent solution and shaken, and the solution was kept at 35 °C. The colored substances in the solution were measured by a UV-visible spectrophotometer until the UV absorption peak intensity at 412 nm did not increase further, and then the formaldehyde concentration in the liquid product was determined by the standard curve. The reagent solution was prepared by dissolving 15 g of ammonium acetate, 0.3 mL of acetic acid and 0.2 mL of pentane-2,4-dione in 100 mL of water.

[0067] The Ag prepared in Example 1-5 27 The nanoclusters were dissolved in dichloromethane and tested for UV-visible absorption spectra. Figure 2 As shown, Ag 27 The dichloromethane solution of the nanoclusters has ultraviolet absorption at 365nm, 558nm and 623nm, especially at 365nm, which shows a strong absorption feature, indicating that Ag 27 Nanocluster photosensitizers have a very good response to 365nm wavelength light sources. Selecting 365nm wavelength LED light source conditions can effectively excite Ag 27 The electrons in the nanocluster photosensitizer transition from the ground state to the excited state, which is beneficial for the TiO2 carrier to improve the efficiency of photogenerated electron-hole separation, thereby achieving efficient photocatalytic hydrogen production.

[0068] The loading rate is 0.5% to 4% Ag 27 @The photocatalytic hydrogen production performance of the TiO2 composite photocatalytic material was tested under the conditions of a 365nm wavelength LED. Figure 3 Ag with different loading rates prepared in Example 6 27 @Linear relationship between TiO2 hydrogen production and illumination time; Figure 4 Ag with different loading rates prepared in Example 6 27 @Hydrogen production performance diagram of TiO2 under 365nm light; Figure 5 Ag with different loading rates prepared in Example 6 27 @Schematic diagram of the determination of formaldehyde content in the solution after photocatalytic hydrogen production by TiO2.

[0069] Figure 3 It shows that the Ag with different loading rates 27 The hydrogen production of TiO2 has a good linear relationship with the illumination time, with the optimal loading rate being 1%. Figure 4 It shows that when methanol is used as sacrificial agent, 1% Ag 27 @TiO2 has the highest hydrogen production rate (15.77mmol·g -1 ·h -1 ), is a commercially available TiO2 carrier (1.30mmol·g 1 ·h -1 ). In addition, the liquid recovery was measured after 4 hours of illumination. Figure 5 The results showed that methanol can be oxidized to form high value-added product formaldehyde. 27 The formaldehyde content in the solution of the @TiO2 composite photocatalyst (37.68mmol / L) is 10.70 times that of the TiO2 carrier (3.52mmol / L). 27Nanoclusters as photosensitizers significantly improve the photocatalytic efficiency of TiO2 under ultraviolet light irradiation, especially in promoting hydrogen generation and formaldehyde formation.

[0070] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A kind of Ag 27 Nanocluster photosensitizer, characterized in that The Ag 27 The chemical formula of the nanocluster photosensitizer is C 170 H 167 Ag 27 Cl2N 18 O6P7, composed of 27 Ag atoms, 3 DPP organic ligands, 6 DPCA organic ligands, 2 DPPB organic ligands, 3 Ac ligands and 2 Cl halogen ligands, is abbreviated as Ag 27 (DPCA)6(DPP)3(DPPB)2(Ac)3Cl2, belongs to the monoclinic system; the space group is C2, α=90°, β=112.278(7)°, γ=90°, The molecular weight is 5758.39Da; The organic ligand DPCA is deprotonated bis(2-pyridylmethyl)amine, the organic ligand DPP is deprotonated diphenylphosphine, the organic ligand DPPB is 1,4-bis(diphenylphosphino)butane, and the ligand Ac is CH3COO - , the structural formulas of the organic ligands DPP, DPCA and DPPB are shown in the following figures:

2. The Ag according to claim 1 27 Nanocluster photosensitizer, characterized in that The Ag 27 Two twisted Ag in nanocluster photosensitizer 13 Icosahedrons are fused together to form Ag by sharing triangular faces 23 , the remaining 4 Ag atoms are respectively 23 The two Ag atoms in the core, the P atom in the diphenylphosphine ligand, and the two N atoms in the bis(2-pyridylmethyl)amine ligand form four μ5-Ag sites. 23 Together with 4 μ5-Ag, it forms the core Ag of the cluster 27 .

3. The Ag according to claim 1 or 2 27 The method for preparing a nanocluster photosensitizer is characterized in that: The steps include: S1. Dissolve the silver salt in a mixed solvent of dichloromethane and methanol, add the monophosphine ligand and the diphosphine ligand, stir, then add the nitrogen ligand and acetic acid, continue to stir well, add the sodium borohydride aqueous solution, stir well at room temperature in the dark, and obtain a green clear solution; S2, using ether as a diffusion agent, gas phase diffusion is carried out into the green clear solution to obtain crystals, collecting the crystal products, washing with ether and vacuum drying to obtain Ag. 27 Nanocluster photosensitizers.

4. Ag according to claim 3 27 The method for preparing a nanocluster photosensitizer is characterized in that: The molar mass ratio of the silver salt, the monophosphine ligand, the diphosphine ligand, the nitrogen ligand, the acetic acid and the sodium borohydride contained in the sodium borohydride aqueous solution is 1:(0.6-1.3):(1.1-1.7):(0.4-1):(2-4):(12-20).

5. The Ag according to claim 3 27 The method for preparing a nanocluster photosensitizer is characterized in that: In step S1, the mixed solvent of dichloromethane and methanol is prepared by mixing dichloromethane and methanol in a volume ratio of (4-5):

1.

6. Ag according to claim 3 27 The method for preparing a nanocluster photosensitizer is characterized in that: In step S1, the silver salt is dissolved in a mixed solvent of dichloromethane and methanol at a concentration of 0.009-0.012 mmol / ml.

7. The Ag according to claim 3 27 The method for preparing a nanocluster photosensitizer is characterized in that: The silver salt is silver trifluoromethanesulfonate; or, the monophosphine ligand is diphenylphosphine hydrogen; or, the diphosphine ligand is 1,4-bis(diphenylphosphino)butane; or, the nitrogen ligand is bis(2-pyridylmethyl)amine.

8. The Ag according to claim 1 or 2 27 Application of nanocluster photosensitizers in photocatalytic hydrogen production.

9. The Ag according to claim 8 27 The application of nanocluster photosensitizer in photocatalytic hydrogen production is characterized by: Ag 27 Nanocluster photosensitizers loaded on TiO2 were applied in photocatalytic hydrogen production.

10. The Ag according to claim 9 27 The application of nanocluster photosensitizer in photocatalytic hydrogen production is characterized by: Ag 27 The loading rate of nanocluster photosensitizer on TiO2 was 1%.

Citation Information

Patent Citations

  • Nuclear defect alloy nanocluster and application thereof in hydrogen production through water photolysis

    CN119076064A